SUBSTANTIATION OF MAIN PARAMETERS OF PROSPECTIVE MILLING PEAT MACHINES - G. A. Basalay (Наука и техника)
Main directions of further modernization of УМПФ-type milling peat machines have been determined on the basis of complex analysis pertaining to application of these machines. Their modernization presupposes successful solution of national economy problem which is to increase a portion of local kinds of fuel in the power engineering balance of the Republic. One of the prospective peat machine diagram proposes to use a wheel propeller with a narrow back axle and front placement of removing and transporting element tool in relation to a bunker while applying a flight conveyer. Using this machine it is possible to obtain an improvement in indices of reliable operation of units, reduction in specific amount of metal per structure, reduction in power consumption in accomplishment of technological operation, higher productivity. First two directions of modernization provide for partial changes in some components of the machine and these tasks are successfully solved at repair and maintenance shops of peat enterprises. The third direction, that is development of milling peat machine of new generation, requires involvement of design organizations and machine-building plants.